The Asia-Europe Meeting: Contributing to a New Global Governance Architecture The Eighth ASEM Summit in Brussels (2010) - Bersick, Sebastian (Amsterdam University Press, 2011)
The Asia-Europe Meeting (ASEM) process was designed in 1996 to bring Asia and Europe closer together. The Asia-Europe Meeting: Contributing to a New Global Governance Architecture focuses on the discussions and results of the eighth ASEM Summit that took place in October 2010 in Brussels. It gives a multifaceted picture of Asia-Europe convergences and disparities and helps to understand how these are dealt with through interregional political dialogue. Renowned academics and observers of Asia-Europe relations provide analysis and essential insights into the advantages and limitations of contemporary ASEM affairs, their most pertinent issues, and the role of ASEM as a constituent of the developing new global governance architecture. In addition, the book offers a unique insider's perspective of the preparations and negotiations of the Brussels events. The Annex of the book furthermore includes ASEM related primary sources not available in any publicly accessible record.